Formation of artistic education in Transcarpathia in the first half of the 20 th century (Pedagogy of Higher and Secondary Education, 2015)
Voloshchuk A. V. Formation of artistic education in Transcarpathia in the first half of the 20 th century.The stages of artistic education development in Transcarpathia in the first half of the 20 th century are revealed. It is emphasized that pedagogical activity and oeuvre of such professional artists as А. Erdely and J. Bokshai gave powerful impulse to creation of Transcarpathian painting school.
Keywords: artistic education; fine art; painting school of Transcarpathia; aesthetic education; school of art